PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI - Hanifah Rizky Dwi Febrianti (2022)
This study aims to determine the effect of institutional ownership, managerial ownership, and corporate social responsibility on tax avoidance with audit quality as moderation variable and profitability, leverage and company size as control variables in the mining and manufacture sector for the 2018-2020 accounting period. This research is a quantitative research that uses secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange (IDX) and the company's official website. This study used a sample of 33 companies and 99 total research datas. Hypothesis testing in this study using the STATA 16 application and by the assistance of Microsoft Excel. Based on the results of the tests that have been carried out, it can be concluded 1) institutional ownership has no effect on tax avoidance 2) managerial ownership has no effect on tax avoidance 3) corporate social responsibility has no effect on tax avoidance 4) audit quality does not moderate institutional ownership for tax avoidance 5) audit quality does not moderate managerial ownership for tax avoidance 6) audit quality does not moderate corporate social responsibility for tax avoidance